Management of the Conduction Independent Curriculum at Buddhist College: Case Study - Budiyanto, Budiyanto; Kabri, Kabri; Surya, Julia (Media Manajemen Pendidikan, 2024)
Due to a fact that the concept is new for both learners and educators, there are several roles that must be taken into account when conducting MBKM. Many issues were discovered as a result of observations performed on several campuses, including the following: 1) Students from multiple campuses took part of learning implementation during the MBKM activity, but many of them were involved in these activities and had varied interests. 2) The phenomenon I discovered regarding the MBKM's actions as though it had not been managed. The researchers pose the research question, "How is the management of the conduction of MBKM in Buddhist Colleges?" The data were collected, reduced, and then evaluated using qualitative research data analysis. Due to a number of issues, including a lack of understanding of MBKM literacy, implementation goals and objectives, a lack of resources, and the fact that many lecturers do not completely grasp how to use MBKM, it appears to be too difficult for Buddhist institutions to implement. The table above also provides information on the requirements for joining MBKM for the reader's understanding. The duties of leaders involve not only acquiring this data but also organizing the next program. Before starting the steps, the leader must understand the directions. Planning, organizing, coordinating, and assessing are the managerial functions, on the other hand, according to academics.